Activation And “Inactivation” Of A Plasminogen Proactivator (Preurokinase) In Human Tissue Culture Media - Wijngaards, G; Bernik, M B (Thrombosis and Haemostasis, 1981)
Besides active plasminogen activators, the synthesis of a proactivator (preurokinase) has been reported in cell and tissue cultures. It is suggested that slow activation of the proactivator in the culture medium occurs by an unknown proteolytic mechanism. Rapid activation can be obtained by incubation with plasmin or trypsin, whereas incubation with thrombin results in a preurokinase which has lost its capacity to be activated. These studies were performed with the fibrin plate method (FPM) which in itself involves further exposure of preurokinase to plasmin over a 16 to 20 hr period.In the present study the effect of incubation of some culture media with plasmin and thrombin, on the activation of proactivator, was measured using the clot lysis time method (CLTM) and an immediate assay with the synthetic substrate S-2322.The results with the CLTM showed that incubation of particular culture media with plasmin increases the activator activity immunologically related to urokinase. Incubation with thrombin was without effect, but when followed by incubation with plasmin a decreased level of activatable preurokinase was found. The decrease correlated positively with the thrombin concentration and incubation time and negatively with previous treatment of thrombin with antithrombin III. The S-2322 method showed very similar results, while comparison of the results of both CLTM and S-2322 method with those of the FPM revealed only small differences. Results indicate that preurokinase is hardly activated by plasmin in fibrinolytic assays, not even during the long incubation time of the FPM. Accordingly, it seems unlikely that there will be a positive feedback in thrombolysis as a consequence of activation of preurokinase by plasmin. (Supported, in part, by NATO Research grant RG 018.80).